2004
DOI: 10.1158/1078-0432.ccr-03-0135
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor 1α Expression as an Intrinsic Marker of Hypoxia

Abstract: Purpose: Hypoxia-inducible factor (HIF)-1␣ expression was studied retrospectively in locally advanced carcinoma of the cervix in relation to other methods for measuring/assessing tumor hypoxia and outcome after radiotherapy.Experimental Design: HIF-1␣ expression was examined in formalin-fixed tumor biopsies using a semiquantitative scoring system and correlated with measurements of hypoxia obtained using oxygen electrodes, pimonidazole staining, and carbonic anhydrase 9.Results: High HIF-1␣ expression showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(79 citation statements)
references
References 30 publications
1
73
5
Order By: Relevance
“…Our finding agrees with a study of 146 Japanese patients, mainly with distal gastric cancer (Urano et al, 2006), and with some published reports showing HIF-1a has no prognostic significance in cervical (Haugland et al, 2002;Hutchison et al, 2004), colorectal (Yoshimura et al, 2004) and ovarian (Birner et al, 2001) cancers. In contrast, two further studies in gastric cancer showed HIF-1a expression was an adverse prognostic factor in multivariate analyses Sumiyoshi et al, 2006).…”
Section: P=082supporting
confidence: 93%
See 1 more Smart Citation
“…Our finding agrees with a study of 146 Japanese patients, mainly with distal gastric cancer (Urano et al, 2006), and with some published reports showing HIF-1a has no prognostic significance in cervical (Haugland et al, 2002;Hutchison et al, 2004), colorectal (Yoshimura et al, 2004) and ovarian (Birner et al, 2001) cancers. In contrast, two further studies in gastric cancer showed HIF-1a expression was an adverse prognostic factor in multivariate analyses Sumiyoshi et al, 2006).…”
Section: P=082supporting
confidence: 93%
“…It has been suggested that HIF-1a expression may be a less important prognostic factor in surgically treated patients as the major influence of hypoxia-induced radiation resistance is lacking (Beasley et al, 2002). However, studies in patients with cervical cancer who underwent radiotherapy showed either a trend towards improved prognosis (Mayer et al, 2004) or an improved prognosis in a subgroup of patients (Hutchison et al, 2004). Although differences in staining and scoring methods cannot be ruled out completely, differences in prognostic outcome observed in numerous studies may reflect the differential regulation by HIF-1a of a range of downstream target molecules.…”
Section: P=082mentioning
confidence: 99%
“…In uterine cervical cancer, some papers (31)(32)(33)(34) reported that overexpression of HIF-1α in pretreatment uterine cervical cancer cells served as a predictive marker for poor prognosis after treatment by radiotherapy. However, there has been no study examining the relationship between the expression of HIF-2α and uterine cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were biopsied 12 -20 h after receiving pimonidazole. A semiquantitative scoring system was used to quantify pimonidazole binding as described elsewhere (Hutchison et al, 2004).…”
Section: Pimonidazole Bindingmentioning
confidence: 99%
“…The staining and scoring methods for MVD (Cooper et al, 1998), VEGF (Loncaster et al, 2000), HIF-1a (Hutchison et al, 2004), HIF2a (Beasley et al, 2002), CA IX ) and Glut-1 (Airley et al, 2001) have been described elsewhere Only tumour nuclear HIF-1a was scored as described elsewhere (Aebersold et al, 2001). All scoring was performed in a double-blind manner by two independent investigators.…”
Section: Mvd Vegf Hif Ca IX Glut-1mentioning
confidence: 99%